Pembuatan tool modeling eksperimen bidang miring dengan pengontrolan sudut kemiringan otomatis untuk analisis video tracker (Experimental inclined plane modeling tool fabrication with automatic tilt angle control for video tracker analysis) - Yolla Octriany; - Asrizal (PILLAR OF PHYSICS, 2019)
One of the experimental science knowledge of physics . Through experimental activities many motion phenomena can be observed, such as the dynamics of motion. One of the dynamics phenomenon of motion that can be done is the motion experiment in the inclined plane. From the observation results, it is known that the motion experiments on the incline were still done manually, namely changing the slope angle and measuring the time on the incline plane experiment still manually to determine the coefficient of kinetic friction, speed, acceleration, and rope tension. The previous set of sloping field experiments had limitations in displaying the results of measurements of physical quantities. One solution to solve the problem was to make modeling tool and analyze it with tracker software . The aims of this research were determine the specification of the performance of experimental modeling tools on the inclined plane, determine the value of kinetic friction coefficient, determine the value of accuracy and accuracy, and determine the effect of changes in tilt angle. This research was a type of engineering research. Engineering research is a design activity that involves things that are relatively new, both in the form of processes or products or prototypes. Data collection was done in two ways, namely through direct and indirect measurement. The direct measurement results of this research were the value of the change in the tilt angle and the indirect measurement results are the values of kinetic friction coefficient, velocity, acceleration, and rope tension in the video software tracker data analysis technique. Based on the results of data analysis four research results can be stated. First, the specification of the performance of the modeling tool on the sloping plane experimental plane with a sliding plane with a length of 50 cm and a width of 10 cm and a base with a length of 40 cm and a width of 10 cm. NEMA 17HS Stepper Motor is used for tilt angle control. Second, the value of the kinetic friction coefficient carried out with the object launch experiment was 0.265. Third, the accuracy value is 93.00% and the accuracy result is 97.00%. Fourth, the greater the tilt angle, the smaller the speed and acceleration values. The value of the rope tension, the greater the angle of inclination, the greater the value of the rope tension.